Analysis of two single-nucleotide polymorphisms (rs2241766 and rs1501299) of the adiponectin gene in patients with coronary artery disease and coronary slow flow - Muhammad Diah; Aznan Lelo; Zulfikri Muhktar; Dharma Lindarto (Medicinski glasnik, 2020)
Aim To investigate the association of two single-nucleotide polymorphisms (SNPs) of the adiponectin gene (+45 T>G [rs2241766] and +276 G>T[rs1501299]) in patients with coronary artery disease (CAD), coronary slow flow (CSF) and in healthy subjects. Methods The study investigated 90 patients: 30 patients with coronary artery disease (the CAD group), 30 with only coronary slow flow (the CSF group) and 30 healthy patients. Genotyping was carried out for two of these SNPs in the adiponectin gene using the TaqMan polymerase chain reaction (PCR) method. Results There were no significant differences in the frequencies of polymorphism +45T>G (rs2241766) genotype (p=0.464) and the allele (p=0.362). There were also no significant differences between the +276 G>T (rs1501299) genotype and the allele (p=0.624 and p=0.281, respectively). Conclusion Our study indicated that in patients with CAD, CSF, and in healthy subjects, the SNP +276G>T and +45T>G alleles of the adiponectin gene were not associated.
Keywords: genetic association; cardiovascular disease; coronary angiography